The general practitioner and mental health problems: challenges and strategies for medical education - Ballester, Dinarte Alexandre; Filippon, Ana Paula; Braga, Carla; Andreoli, Sérgio Baxter (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Within the context of primary health care and mental disorders, our aim was to study the opinions of general practitioners regarding attendance of people with mental health problems. DESIGN AND SETTING: Qualitative focal group study among primary care services in the cit- ies of Porto Alegre and Parobé, State of Rio Grande do Sul. METHODS: A deliberately selected sample of 41 general practitioners who were working in basic health services met in focal groups. Two videos were presented, which simulated consultations for patients with depression and psychoses. The discussions about the identiﬁcation and handling of mental health problems were recorded and assessed via content analysis. RESULTS: The opinions related to the difﬁculties of diagnosing and treating mental problems, the involvement of relatives in caring for patients, the difﬁculty of compliance with the treatment, the uncertainty experienced by physicians and the difﬁculty of referring patients to specialized services. CONCLUSIONS: The general practitioners indicated that they perceived the mental health problems among their clientele, but the diagnosis and treatment of these problems are still seen as a task for specialists. The challenge of continuing education on mental health requires methods of interactive and critical teaching, such as the problem based approach.